Linear analysis of Latin origin Turkish alphabet(Script Italic hand writing example) - (:unkn) unknown (Sakarya University, 2015)
It is especially important during the first class that the teacher knows the subject well and has the necessary skills to apply the alphabet both on the board and on the student notebooks. Writing success is increased if he/she shows the anatomic structures, line spacings and guidelines using colored chalks on the board. Similarly, applications on the student notebooks also enable reinforcement. The linear classification of letters is especially important during the writing courses at education faculties that educate teachers. The status of each is important for the classification of upper and lower case letters. Alphabet will be examined by way of drawing as well as explanatory expressions by classifying letters as slanted, wavy, curvy letters due to their anatomic structure, letters with curved lower extension, letters with round bend on the line, letters with a bowl, ‘S’ letters, letters with dots, letters with similar anatomic bodies, letters with extensions towards the top or bottom, letters with flat starts etc. Thus, teacher candidates will gain the sensitivity of artists with a wide field knowledge and application regarding letters which are the fundamental elements of writing. The proper and effective learning of the alphabet by the teachers will contribute to the education of students in the future. © The Turkish Online Journal of Educational Technology.